Three Amarna Essays - Liverani, Mario
Introduction and Translation by M. L. Jaffe; Pharaoh's Letters to Rib-Adda, OA 10 (1971) 253ff.; Social Implications in the Politics of Abdi-Aširta of Amurru, RSO 40 (1965) 267ff.; Irrational Elements in the Amarna Trade, OA 11 (1972) 297ff.